A complicated infection by cutaneous Nocardia wallacei and pulmonary Mycobacterium abscessus in a Chinese immunocompetent patient: a case report - Qin, Ling; Wang, Sidan; Zheng, Zhifen; Zhang, Wenqian; Qu, Qiang; Li, Jun; Tan, Yurong; Cao, Liming (Frontiers in Cellular and Infection Microbiology, 2023)
Nocardiosis is an infectious disease caused by Nocardia that primarily affects immunocompromised hosts. Mycobacterium abscessus is a common opportunistic pathogen that causes disease in humans, including pulmonary and extrapulmonary infection. Nocardia spp. infection is uncommon, and infection with Nocardia wallacei and Mycobacterium abscessus is even rarer. A 59-year-old immunocompetent woman with risk factors for environmental exposure developed nocardiosis and presented to the hospital with a cough, shortness of breath, hemoptysis, and a back abscess. An enhanced computed tomography (CT) of the chest revealed partial destruction of the right lung, as well as consolidation of the right upper lobe. Rare pathogens N. wallacei and Mycobacterium abscessus were detected by metagenomic next-generation sequencing (mNGS) from abscess on the back and lung puncture tissue, respectively. She was treated with a combination of antibiotics and was finally discharged with a good prognosis. In this case, we present a patient who was successfully diagnosed with N. wallacei and Mycobacterium abscessus infection using mNGS. This importance of 2 This is a provisional file, not the final typeset article using mNGS in pathogen detection and the effective use of antibiotics in treating patients with longterm rare infections is highlighted in this report.